Impact of Treatment Duration in First-Line Atezolizumab Plus Chemotherapy in Extensive-Stage Small-Cell Lung Cancer: A Multicenter Real-World Retrospective Study - Mehmet Nuri Baser; Bilgin Demir; Gamze Serin Ozel; Gamze Gokoz Dogu; Serdar Karakaya; Mucahit Ugar; Naziye Ak; Ahmet Ozveren; Ufuk Camanlı; Olcun Umit Unal; Merve Turan; Esin Oktay (Medicina, 2025)
Background and Objectives: Small-cell lung cancer (SCLC) is an exceedingly aggressive neoplasm distinguished by an unfavorable prognosis. Recent studies have confirmed chemo-immunotherapy as the conventional first treatment for extensive-stage small-cell lung cancer (ES-SCLC), but the impact of treatment duration remains unclear. The goal of this study was to find out how the length of treatment affected progression-free survival (PFS) and overall survival (OS) in patients with ES-SCLC who were receiving first-line atezolizumab plus chemotherapy. Materials and Methods: This retrospective multicenter study comprised 82 patients from six oncology centers in Turkey between 2017 and 2024. Patients were categorized into two categories according to the quantity of chemotherapy cycles they had undergone: standard treatment (≤4 cycles) and extended treatment (≥5 cycles). For the purpose of analyzing survival outcomes and related clinical determinants, as well as the demographic structures and features of the patients, both univariate and multivariate Cox regression models were utilized. Results: The median number of atezolizumab cycles was 8 (1–63). OS was 29.46 months after 15.8 months of follow-up, while PFS was 10.63 months. When comparing the two groups, we found no statistically significant differences in either PFS (p = 0.952) or OS (p = 0.374). Significant associations with OS were seen in the standard therapy group for both ECOG PS 1 (p = 0.028). Thoracic radiation considerably decreased progression risk (HR = 0.41, p = 0.031) in the extended group. Conclusions: While prolonging chemo-immunotherapy beyond four cycles did not significantly improve survival, the selected patient subgroups may benefit from personalized approaches. Thoracic radiotherapy emerged as a key modifier of outcome.